Synthesis, Corrosion Inhibition Efficiency in Acidic Media, and Quantum Chemical Studies of Some Hydrazine Derivatives - Abood, Huda Saleh; Jasim, Ekhlas Qanber; Muhammad-Ali, Munther Abduljaleel (Science and Technology Indonesia, 2024)
In this work, four hydrazone Schiff base derivatives N-(2,4-Dinitro-phenyl)-N’-(1H-pyrrol-2-ylmethylene)-hydrazine (1a), N-Benzo [1,3] dioxol-5-ylmethylene-N’-(2,4-dinitro-phenyl)-hydrazine (1b), (E)-5-((2-(2,4-dinitrophenyl)hydrazono)methyl)-2-hydroxybenzoic acid (1c) and (E)-1-(2,4-dinitrophenyl)-2-(2-methoxybenzylidene)hydrazine (1d) were synthesized by reaction of four aldehydes namely pyrrole-2-carboxaldehyde, piperonal, 5-formylsalicylic acid, and o-vanillin with 2,4-dinitrophenyl hydrazine to produce the final compounds 1a, 1b, 1c, and 1d, respectively. These four compounds were investigated as corrosion inhibitors in aqueous mild acidic static solution. FTIR, HNMR, and elemental analysis were used to elucidate the chemical structure of the synthesized inhibitors. Using potential dynamic polarization measurements, these inhibitors’ efficiency in preventing C-steel corrosion in 1.00 M HCl was studied. The results of the experiments revealed that 1×10−3 M is the ideal concentration for 1a, 1b, 1c, and 1d, and that the corresponding inhibition efficiencies for these subunits were 80.70%, 91.30%, 91.34, and 88.80%, respectively. The best corrosion inhibitors were compounds 1b and 1c. Furthermore, studies suggested that these substances are mixed-type inhibitors and that the efficiency of the inhibition is strongly correlated with their quantity. Quantum paraments included Dipole moment, energy band gap (ΔE), value of energy of lowermost unoccupied molecular orbital (ELUMO), and energy of high most occupied molecular orbital (EHOMO) using Molecular Operating Environment MOE, Gaussian, and HyperChem software packages were determined which demonstrated strong agreement between algorithmic and practical findings.